2018
DOI: 10.1557/adv.2018.508
|View full text |Cite
|
Sign up to set email alerts
|

Delivery of Immunomodulatory Microparticles in a Murine Model of Rotator Cuff Tear

Abstract: Full thickness rotator cuff tears (RCT) and the associated muscle degeneration that results due to this injury presents a significant clinical burden. The prevention or recovery from this degeneration requires the synchronized behavior of many cells that participate in regeneration. Strategies that tune the inflammatory cascade that is initiated after injury serves as a powerful way to influence tissue repair. Here, we use the local, sustained delivery of the immunomodulatory small molecule FTY720 to examine w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 21 publications
(16 reference statements)
0
2
0
Order By: Relevance
“…In recent years, several landmark studies have shown that the release of immunomodulatory drugs from implanted biomaterials can modulate the behavior of host monocytes and macrophages, with beneficial effects in treating disease and tissue injury [11,[54][55][56][57]. For example, the release of the S1P receptor agonist FTY720 recruits regenerative monocytes and macrophages to promote tissue regeneration [57][58][59]. However, the release of drug from biomaterials may affect all cells in the vicinity, not just macrophages, increasing the potential for off-target effects.…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, several landmark studies have shown that the release of immunomodulatory drugs from implanted biomaterials can modulate the behavior of host monocytes and macrophages, with beneficial effects in treating disease and tissue injury [11,[54][55][56][57]. For example, the release of the S1P receptor agonist FTY720 recruits regenerative monocytes and macrophages to promote tissue regeneration [57][58][59]. However, the release of drug from biomaterials may affect all cells in the vicinity, not just macrophages, increasing the potential for off-target effects.…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, several landmark studies have shown that the release of immunomodulatory drugs from implanted biomaterials can modulate the behavior of host monocytes and macrophages, with beneficial effects in treating disease and tissue injury 11,[54][55][56][57] . For example, the release of the S1P receptor agonist FTY720 recruits regenerative monocytes and macrophages to promote tissue regeneration [57][58][59] .…”
Section: Discussionmentioning
confidence: 99%